Electronic Evidence in Indonesian Judiciary: An Analysis of the Principle La Yunkaru Taghayyur Al-Ahkam Bi Taghayyur Al-Zaman - Panji Anugrah; Musliadi; Imran Anwar Kuba; Achmad Musyahid (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
Digital transformation has significantly reshaped the evidentiary system within the Indonesian judiciary, particularly through the recognition of electronic evidence such as emails, chats, and digital documents. This shift raises critical issues regarding the legitimacy and limitations of such evidence from the perspective of Islamic law, which traditionally relies on the concept of bayyinah. This study aims to analyze the validity and boundaries of electronic evidence by employing the legal maxim L? yunkaru taghayyur al-a?k?m bi taghayyur al-zam?n as an analytical framework. The research adopts a normative qualitative method with approaches rooted in usul al fiqh, statutory analysis, and conceptual examination. Data sources include classical and contemporary Islamic legal texts, legal maxims, statutory regulations, and relevant academic literature. The findings indicate that electronic evidence can be accepted as valid within Islamic law by positioning it as a form of modern qarinah, provided it meets criteria of authenticity, integrity, and relevance. However, such acceptance is not absolute, as it must remain within the boundaries of justice and public interest. Therefore, a structured evaluative framework is essential to ensure that the use of electronic evidence aligns with the fundamental objective of achieving truth and justice.